Volcanic Ash Layers of the Eyjafjalla over Europe in April/May 2010 - Characterized by the DLR-Falcon Aircraft and by Ground-based Lidars - Weinzierl, Bernadett; Minikin, Andreas; Reitebuch, Oliver; Dahlkötter, F.; Schlager, Hans; Rahm, Stephan; Hamburger, T.; Gasteiger, J.; Freudenthaler, Volker; Groß, Silke; Wiegner, M.; Ansmann, A.; et al. (2010)
In April/May 2010 large areas of the European airspace were impacted by volcanic ash layers originating from the Eyjafjalla volcano in Iceland. Between 19 April and 18 May 2010, the DLR-Falcon performed 17 research flights in aged (up to 120 h) volcanic ash plumes over Central and Western Europe, but also in a young (7 h) plume close to the volcano in Iceland. The Falcon was instrumented with a downward looking, scanning 2-μm-Wind-Lidar (aerosol backscattering and horizontal wind, 100 m vertical resolution), and several in situ instruments. The aerosol in situ instrumentation, including wing station probes (PCASP, FSSP-300, 2D-C), covered particle number, size, and chemical composition in the size range between 5 nm and 800 μm. Further in situ instruments measured O3, CO, SO2, H2O, and standard meteorological parameters. When possible, the flight path of the Falcon was directed to pass over various ground-based lidar stations like Munich-Maisach, Leipzig, Hamburg, Stuttgart, Jülich, and Cabauw. Volcanic ash layers were detected at altitudes between 1 and 6 km. The layers had a depth between 0.1 and 3 km and spread several 100 km in the horizontal. Sometimes the volcanic ash plumes showed a multi-layer structure. Altogether 35 flight legs were identified, when the Falcon was inside a volcanic ash plume. The maximum ash mass concentrations and SO2 mixing ratios measured in the young plume were about 1 mg m-3 and 150 nmol mol-1, respectively. The chemical composition of single particles was derived by means of scanning electron microscopy from impaction samples. Particles were mainly composed of secondary sulphate and silicate minerals and showed a crystalline structure. Volcanic glass was not present in the samples investigated. The element chemical composition of the particles was used to constrain the complex index of refraction, which is important for the derivation of the particle size distribution from optical particle counters. In this talk, we give a short overview of the DLR-Falcon research flights in ...